Evolution of green energy and vehicle technology special topic volume with peer reviewed papers only - Saravanan, S. (Applied mechanics and materials ;, 2015)
Collection of selected, peer reviewed papers from the National Conference on EVOLUTION OF GREEN ENERGY AND VEHICLE TECHNOLOGY, March 2-3, 2015, Sriperumbudur, India.The 20 papers are grouped as follows:Chapter 1: Engineering Decisions for Systems of Alternative EnergyChapter 2: Fuels and EnginesChapter 3: Engineering Decisions in Automotive Industry.